1972
DOI: 10.1111/j.1432-1033.1972.tb01711.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Microsomal Ethanol Oxidation

Abstract: Microsomes from rat liver form hydrogen peroxide in the presence of an NADPH-generating system in proportion to protein concentrations as determined by three independent methods : ferrithiocyanate, cytochrome c peroxidase, and scopoletin fluorescence. Maximal rates observed were about 15 pmol H,O,/g microsomal protein per minute. The oxygen concentration for half-maximal rates was 50 pM. It is suggested that NADPH-dependent hydrogen peroxide formation in microsomes is mainly due to NADPH oxidase; however, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
192
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(200 citation statements)
references
References 27 publications
8
192
0
Order By: Relevance
“…Dinitrophenol-activated ATPase: controls, 88.8 ±14.6 (5); chronically ethanol-treated, 90.2±9.8 (5)]. Lieber & de Carli (1970a) and Carter & Isselbacher (1971) have reported that the liver microsomal NADPH oxidase, an enzyme system which produces H202 (Gillette, et al, 1957;Thurman et al, 1972), is increased after chronic ethanol treatment. An increased rate of H202 production might be in part responsible through the catalase mechanism for the greater rate of ethanol metabolism after chronic ethanol treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinitrophenol-activated ATPase: controls, 88.8 ±14.6 (5); chronically ethanol-treated, 90.2±9.8 (5)]. Lieber & de Carli (1970a) and Carter & Isselbacher (1971) have reported that the liver microsomal NADPH oxidase, an enzyme system which produces H202 (Gillette, et al, 1957;Thurman et al, 1972), is increased after chronic ethanol treatment. An increased rate of H202 production might be in part responsible through the catalase mechanism for the greater rate of ethanol metabolism after chronic ethanol treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It appears, therefore, that in vivo the production of H202 is rate-limiting (Aebi, 1960;Portwich & Abei, 1960). Lieber & De Carli (1970a) and Carter & Isselbacher (1971) have reported that a microsomal NADPH oxidase, an enzyme system that can produce H202 (Gillette et al, 1957;Thurman et al, 1972), is increased in rats treated chronically with ethanol. Thus an increased H202 production could conceivably cause an increased metabolism of ethanol by catalase.…”
mentioning
confidence: 99%
“…H202 was determined by the method of Thurman et al (51). Briefly, to stimulated PMNs in HBSS + azide, 200/~1 of TCA (30%) were added.…”
Section: Determination Of Hydrogen Peroxide (11202)mentioning
confidence: 99%
“…At different time points, samples were taken and the reaction was terminated by adding 12.5% (w/v) TCA. Peroxide concentration was determined with the ferrithiocyanate assay (Thurman et al, 1972).…”
Section: Peroxidase Assaysmentioning
confidence: 99%